IMPROVING THE STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT BY APPLYING MIND MAPPING TECHNIQUE - Frida Dian Handini; Amrin Saragih (Universitas Negeri Medan, 2013)
AbstractThis study aims to discover the effect of applying Four Square Graphic Organizeron students’ achievement in writing descriptive text. It was conducted by usingexperimental research design. The population of this research was the seventh(VII) grade students of SMP Sultan Iskandar Muda Medan with four parallelclasses. The samples of the research were two classes divided into two groups,experimental and control group which were chosen by using random samplingtechnique. Fifty students were taken as the samples. The experimental group wastaught by using Four Square Graphic Organizer, while the control group wastaught by using freewriting technique. The instrument for collecting the data was awriting test. Pearson Product Moment formula was applied to obtain the reliabilityof the test. Based on the calculation, it shows that the reliability of the test was0,84 categorized as high reliability. Then, after analyzing the data, it was foundthat the value of tobserved was 3,66 with the degree of freedom (df)=48 at the levelof significance p(0,05) = 2,01. It means that tobserved is higher than ttable (3,66 >2,01). The result of this study shows that Four Square Graphic Organizer has asignificant effect on students’ achievement in writing descriptive text.Keywords: writing, descriptive text, Four Square Graphic Organizer,experimental research